Favourable surface properties of boron-doped diamond electrodes for aluminium electrodeposition from ionic liquids - Veder, Jean-pierre; Horne, M.; Rüther, T.; Bond, A.; Rodopoulos, T. (Elsevier Inc., 2012)
Aluminium electrodeposition on a boron-doped diamond (BDD) electrode was studied in the ionic liquid: 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, [C 4mpyr][NTf 2]. Cyclic voltammograms recorded on BDD electrodes in 1 m solutions of AlCl 3 in [C 4mpyr][NTf 2] were compared with those recorded on Au, Al and glassy carbon (GC) electrodes. The BDD electrode exhibits similar voltammetric responses for Al electrodeposition as on metallic electrodes but without interferences from alloy formation or reaction of the electrode material. Conversely, nucleation and growth of Al is significantly more difficult on freshly abraded GC. The electrochemical stability and activity of BDD over a wide potential range make it a highly favourable surface for studying metal deposition at very negative potentials in ionic liquids. © 2012 Elsevier B.V.